CT imaging and staging of carcinoma oesophagus - Chandna, Parveen; B., Siddesh M.; U., Jeevika M.; Kochar, Praveen Kumar T. (International Journal of Research in Medical Sciences, 2017)
Background: Over the past decades, computerized tomography (CT) technology has led to an early detection of cancers and thereby decreasing mortality rate. The objective was to demonstrate usefulness of Toshiba Activion 16 slice multi detector computerized tomography (MDCT) scan in staging of oesophageal cancer. Methods: The study was carried out in the Department of Radio diagnosis, Bapuji Hospital and Chigateri Government Hospital attached to Jagadguru Jayadeva Murugarajendra Medical College, Davangere, Karnataka, India over a period of 24 months. After taking a properly informed written consent, complete history and thorough clinical examination was done and these patients were subjected to CT scan. Results: The total numbers of patients studied in present study were 25. Out of which 10 were males and 15 were females. There were 6 patients upto the age of 54 years and 8 patients equal to or greater than 65 years of age, there were 11 patients between 55-64 years of age. Dysphagia was the most common symptom in patients and was present in all the 25 patients of present study. Other common symptoms were weight loss followed by pain in throat. Two different types of wall thickenings of the involved portion have been reported. The most common asymmetrical wall thickening was observed in maximum number of patients 18 (72%) and circumferential wall thickening was observed only in 7 number (28%) of patients out of 25 total patients showing heterogeneous/homogeneous enhancement. Lower third (40%) and middle third (40%) of the esophagus was the most common site of involvement with regards to location of oesophageal cancer followed by upper third (20%) of the esophagus. Homogeneous wall attenuation was observed in most of the cases accounting for (64%). The other type of wall attenuation noted were heterogeneous (36%). Conclusions: By performing endoscopy uncertainty lies in discrimination of muscular layer from serosal layer in most parts of esophagus. However, by employing MDCT technique separation of 2 layers of esophagus can be better judged. Therefore, MDCT has been found to be the most valuable and preferential technique for planning operational strategy.